Job Motivation as Mediator of Employee Competence and Performance in Sustainable Tourism Industry - M Ikhwan Maulana Haeruddin; Annisa Ciptagustia; Muhammad Yushar Mustafa; Rahmawati Rahmawati; Muh Al Fatah Arief Putra (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study examines the relationship between employee competence, job motivation, and employee performance, with particular attention to the mediating role of job motivation in the hotel industry in Makassar, Indonesia. Research Methodology: A survey-based quantitative design was employed using data from 149 active hotel employees. The data were collected through structured questionnaires and analysed using validity and reliability tests and Partial Least Squares Structural Equation Modelling. Results: The findings reveal that employee competence has a positive and significant effect on both job motivation and employee performance. However, job motivation does not significantly affect employee performance and does not significantly mediate the relationship between employee competence and employee performance. Conclusions: Employee competence is the most decisive predictor of employee performance in the hotel context. Although competence strengthens job motivation, motivation does not function as a significant intervening mechanism in the competence-performance relationship. Limitations: This study is limited to hotel employees in Makassar, applies a cross-sectional design, and relies on self-reported questionnaire data. Contributions: This study contributes to human resource management and hospitality literature by showing that competency development is more directly associated with employee performance than motivational mediation. Practically, the findings suggest that hotel managers should prioritise competency-based human resource strategies, including training, coaching, performance appraisal, and service capability development.